LA ACTUACIÓN ECL ESIAL DE LA RECONCILIACIÓN EN CHILE. - CONTRERAS VILLARROEL, CRISTIÁN (Humanitas (07172168))
The article is about the role of the Church in Chile in the process of reconciliation after the coup d'état of 1973. Important milestones are mentioned, such as the Holy Year of 1975, the National Eucharistic Congress of 1980, the Mission for Life and Reconciliation of 1985, and the visit of Pope John Paul II in 1987. The Chilean Church sought to promote reconciliation through the pastoral option for life and the moral imperative of the task of reconciliation. The role of the Church in defending democratic values and citizen participation is also highlighted. The Church in Chile emphasizes the importance of values such as truth, justice, freedom, and love, and acknowledges the existence of vices that go against these values and have contributed to the moral crisis in the country. The Church poses the challenge of establishing an institutionality that guarantees these values and promotes national reconciliation. The visit of Pope John Paul II in 1987 was an important milestone in this process of reconciliation, and the importance of truth and justice in achieving social reconciliation was emphasized. In subsequent years, the National Commission for Truth and Reconciliation was created to clarify the truth and seek justice in the country. The article discusses the role of the Church in reconciliation in Chile. It is mentioned that Pope John Paul II wished for the country to transition towards the full implementation of democratic institutions. The importance of recognizing sin and forgiveness in the process of reconciliation is highlighted. It is mentioned that the Church felt called to the ministry of reconciliation due to the increasing violence in the country. It is also mentioned that the Church sees itself as a servant of the integral human being and defender of human rights. The Church considers one of its most important actions to be a sign and instrument of union with God and the unity of humanity, as established in the Second Vatican Council. This statement was made in the Dogmatic Constitution on the Church, Lumen gentium, on November 21, 1964.